Labor Unions, Adjuncts, and the Mission and Identity of Catholic Universities. Issue 1 (21st May 2015) - Beyer, Gerald J.
Abstract : Catholic social teaching (CST) has long endorsed the right of all workers to unionize. However, many US Catholics exhibit an antiunion bias. In addition, Catholic institutions have engaged in union busting, thereby flouting CST. Focusing on the recent efforts of adjuncts to unionize at Catholic universities, this article argues that union busting jeopardizes the faith and conscience formation of students and undermines the evangelizing mission of Catholic universities. The article debunks the appeal to religious liberty by Catholic institutions to circumvent the National Labor Relations Board's injunctions to allow adjuncts to unionize. It also refutes the argument that the National Labor Relations Act imposes a style of collective bargaining contrary to the harmonious vision of labor relations in CST. Succinctly stated, the article contends there is no legitimate reason for Catholic universities to thwart the unionization efforts of adjuncts, particularly given the systematically unjust work conditions many of them face.